Studying Policy Changes in Disaster Management in India: A Tale of Two Cyclones. (19th October 2015) - Jha, Ayan; Basu, Rivu; Basu, Atreyee
Abstract: Objective: The mainstay of India's disaster management policy until the early 2000s had been relief and rescue operations. The Odisha Super Cyclone (1999) with 10, 000 deaths and US $3 billion economic damage provided a rude awakening. Recognizing the importance of preemptive preparedness, the government initiated systematic steps to implement a national framework interlinking economic, environmental, and overall developmental issues for efficient response to and mitigation of disasters. Methods: We attempted a critical analysis of this paradigm shift in India's disaster management policy through the prism of 2 cyclones, 14 years apart in time. Results: With improved preparedness and response measures, the death toll in 2013 Cyclone Phailin was 0.5% and the economic loss was about one-third of that during 1999. Concomitant improvements in the technological expertise of the early warning system, an integrated approach at all levels of administration including joint planning with major nongovernmental organizations, and improved community participation were identified as game-changers. An unbelievable 1 million people were evacuated to safety. Conclusions: Our essay aims to highlight key steps in this success and calls for futuristic approaches like insurance programs and gender-sensitive recovery plans. With thorough scrutiny, India's model may well stand to be replicated in resource-restricted settings. ( Disaster Med Public Health Preparedness . 2016;10:42-46)